Os acordos MEC-USAID no Jornal o Estado de S. Paulo (1962 -1973) - Rossi, Pamela de Mattos (2018)
This dissertation aims to analyze and discuss the news published in the newspaper, O Estado de São Paulo (OESP) from 1962 to 1973, relating to bilateral technical and financial 'help' established between Brazil and United States of America, in order to reform and revamp the country's education in all degrees of education. Through the signing of agreements between the Ministry of Education and Culture and Agency for International Development (USAID), known as, historically, MEC-USAID agreement. To this end, investigates the agreements and representations, as such idea was organizing in terms of speeches produced by OESP. It has been by chance that the journal played the role of a trainer of public consensus making the necessary arrangements for the so stage of national education. For the development of this research, were analyzed one hundred and eighty-six (186) national editions of OESP, considering the following criteria from observation of information from a database: a) categorization of news by main themes; b) analysis of news and editorials, considering the position of OESP newspaper, before and after the civil-military coup (1964). Were also analyzed legal and official documents on the theme. It was notice that OESP centralized discussions around the agreements formulated for Advise and Planning of Higher Education, and fluctuated between criticism and criminalization of movements opposed to the establishment of such agreements, particularly in relation to the National Union of Students (UNE)